PENDAMPINGAN PROMOSI DESTINASI WISATA DESA AIK BUKAQ SEBAGAI DESA WISATA DI KABUPATEN LOMBOK TENGAH - Aulia, Maulidya Rahmi; Pertiwi, Linda; Wijaya, Inta Hikna; Hashifa, Alya Maureen; Setiawan, Dawam; Hemawan, Rizal Hendri; Jorgi, Tomas; Bagaskara, Lalu Satria; Adawiyah, Rabiatul; Risma, Ni Kadek Anggitha Yulia (Universitas Mataram, 2023)
Aik Bukaq Village is a village in North Batukliang District, Central Lombok Regency. The village has abundant natural wealth and tourist destinations. Aik Bukaq Village has several tourist destinations including the Aik Bukaq swimming pool, Tereng Kuning tourism, and a reservoir whose water is sourced directly from mountain springs. The KKN program aims to do community service in solving village problems in the field of tourism, namely promotions such as snacks or natural tourist destinations. The outputs expected from the KKN program are: 1) Leaflets related to Appropriate Technology applied; 2) Scientific article entitled